Synergistic Effects of HRM Practices on Nurse Caring Behavior: A Multivariate Analysis in Private Hospitals - Noor Arida Sofiana (Jurnal Relevansi : Ekonomi, Manajemen dan Bisnis, 2026)
Nurse caring behavior is a crucial indicator of nursing service quality, which is influenced by Human Resource Management (HRM) practices in the healthcare sector. This study aimed to analyze the multivariate relationship between organizational commitment, effective communication, and work environment, and caring behavior among inpatient nurses at private hospitals in Bekasi Regency. A cross-sectional design was employed, with 94 nurses as respondents. Data were collected using structured questionnaires and analyzed using canonical correlation analysis. The findings revealed that the first canonical function was significant, with Rc= 0.822 and Rc²= 0.676, indicating that 67.6% of the variance in caring behavior was explained simultaneously by the three HRM factors. The work environment emerged as the most dominant contributor based on canonical loading, whereas organizational commitment demonstrated the largest relative contribution, based on canonical weight. Hospital managers should prioritize strengthening nurses' affective commitment through recognition and a supportive climate rather than relying solely on technical communication training. The study concludes that fostering a conducive work environment and enhancing nurses' organizational commitment are essential for promoting caring behavior and improving nursing service quality in private hospitals.